Unequally Spaced Channels Wavelength Division Multiplexing System - Yasser, Hassan (University of Thi-Qar Journal of Science, 2008)
The channels contributed in creating new pulse during the four-wavemixing (FWM) process are a subject of two features: the first is the fact thatall channels are not working with probability %100 , but with p probability. Second, the bits transmitted are not all "1". Therefore, the equation of power generated using these features should be corrected. Onthe other hand, the use of equally spaced channels wavelength divisionmultiplexing(ESCWDM)system causeanincreaseinthenumberofnew components generated that interfere with the active channels and increase the bit error rate. In order to reduce these interferences, we have providedan unequally spaced channels wavelength division-multiplexing (USC WDM) system composed of several sets. Each set consists of only fourchannels, which locations have been selected to cause no interferences between them. Neighboring sets are separated by a frequency spacing whichshould be large enough to reduce the interferences between the sets, andsmall enough to increase the total number of channels of the system.